Fundamentals of designing rational slab steel-reinforced concrete structures and elements of floors - Galinska, Tatiana; Ovsii, Dmytro; Ovsii, Oleksandra; Ovsii, Mykola (Academic journal Industrial Machine Building Civil Engineering, 2022)
The article provides a general methodology for calculating and designing rational (optimal) slab structures and elements of steel-reinforced concrete (SRC) floors, taking into account the ultimate stress-strain state of their elements at the moment of their destruction. The method of rational (optimal) design of slab SRC elements of floors depending on the ultimate stress-strain state at the time of failure of their component parts includes the solution of two problems: the selection of the cross section of the slab SRC element and its reinforcement, which is a direct task of optimization design; checking the bending strength in the calculated cross-sections of the slab SRC element
Keywords: steel-reinforced concrete; slab structures; flexural strength; floors; design